Runner technology in corporation / Muhammad Razif Roslan ...[et al.] - Roslan, Muhammad Razif; Zakaria, Muhammad Syazwan; Nik Mohd Taufik, Nik Nur Izzati; Ismail, Nuha; Tengku Addee Azreemee, Tengku Anis Fatimah (2016)
"RUNNERZZ" is an application for individual or business who registered through our application that provided pickup and delivery services to customers. This application is to ensure the delivering process is at the right time and the right place. This application is user friendly to operate and maintain; also it is a unique application because consist of several element.